Penerapan Sensor Ultrasonic SRF05 Berbasis Mikrocontroller ATMega 8535 Untuk Sistem Pengereman Otomatis - Eri Riana (Journal of Information System Research (JOSH), 2021)
Transportation technology using electric energy is growing. Electric cars are increasingly being used to reduce fuel oil usage. In addition to the increasingly sophisticated performance of electric cars, the vehicle safety system must also be improved. The existence of Artificial Intelligence is one of the developments in technological sophistication in a world that is increasingly unstoppable and unavoidable. One of the most popular luxury cars in Indonesia, one of which is the Tesla, which is a sophisticated car with the support of an artificial intelligence system, making Tesla an electric car with an automatic control vehicle feature that can run without using a human driver and can provide safety protection for the driver by using automatic braking system in case of an unexpected accident. This journal proposes a future concept design for the forerunner of automatic braking for electric cars using the ATMEGA 8535 microcontroller as the main automatic control and ultrasonic distance sensor. The PWM signal from the microcontroller is used to adjust the speed of the DC motor as the main driving force of the vehicle. The display of the distance between the vehicle and the obstacle can be seen on the LCD and the buzzer is used as an indicator of the safe distance of the car. The experiment was carried out using an RC car with the area to be protected> 500cm (5m), if the SRF05 ultrasonic sensor detects an obstacle at that distance, the SRF05 ultrasonic sensor will send a signal to the microcontroller and turn on an alarm in the form of a buzzer so that the SRF05 ultrasonic sensor will stop signal propagation.